متعاطي المخدر بين العلاج والعقاب "ومضات في التشريع الجنائي الليبي" - العمامي , إيمان علي سالم (Scientific Journal of University of Benghazi, 2023)
In this research, tagged with drug abusers between treatment and punishment, “Flashes in the Libyan Criminal Legislation,” sheds light on a very sensitive topic because it is linked to social, psychological, human and human data as well, as well as its criminal legal dimension, in order to determine the efficacy of the criminal treatment of drug abusers and calibrate it regionally and internationally and in light of The goals for which it was initiated, and our way of doing that was a critical, analytical, critical look at the provisions regulating that treatment, and perhaps one of the most important results of the research is its monitoring of many of the virtues in the criminal treatment of drug abusers, and then followed by a number of recommendations mitigating the severity of those shortcomings, hoping that you will find Its way towards reality in pursuit of drawing the parameters of an optimal criminal policy for drug abusers.